Small Cell Carcinoma of Bladder; Still A Diagnostic and Therapeutic Challenge: Seven Years of Experience and Follow-up in A Referral Center - Kaffash Nayeri, Reza; Sadri, Mohammad; Shahrokh, Hossein; Abolhasani, Maryam; khaleghimehr, Farhood; Zolfi, Ehsan; Yousefzadeh Kandevani, Naser; Kashi, Amir Hossein (Urology Journal, 2020)
Purpose: To report clinical, histopathological, and treatment features of small cell carcinoma of (SmccB) bladder during 7 years in a referral center. Methods: The clinical, histopathological features, treatment modalities, and outcome of all patients with bladder SmccB treated between 2009 and 2016 who were managed in Hasheminejad Kidney Center (HKC) were retrospectively collected. Results: Thirteen patients were diagnosed and managed with SmccB. The average age of patients was 64.92 years. For each patient, 8 markers were used for IHC staining on average. Neuroendocrine markers such as CD 56, Neuron Specific Enolase, Synaptophysin, and Chromogranin were found in a significant percentage of patients (69%, 38%, 54%, and 31% respectively). Patients were managed with TURBT alone (N=3), chemotherapy after TURBT (N=4), chemotherapy plus radical surgery (N=4) and radical surgery alone (N=2). The best clinical result was seen in chemotherapy received patients with or without radical surgery. The mean(SE) of survival rate in patients who received only chemotherapy alone was 42.4 (10.0) months, while in those who were managed with chemotherapy plus radical surgery it was 47.7 (10.1) months. Conclusion: In our center immunohistochemistry was needed for definitive diagnosis in 17/19 samples. Misdiagnosis happened in two samples without IHC request. We think that use of immunohistochemistry should be mandatory for diagnosis of SmccB to exclude misdiagnosis. Chemotherapy is the most important part of treatment and the addition of radical surgery can slightly improve patients’ survival.